2017
DOI: 10.1016/j.juro.2016.07.084
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Underestimation of Prostate Cancer Geometry: Use of Patient Specific Molds to Correlate Images with Whole Mount Pathology

Abstract: Purpose We evaluated the accuracy of magnetic resonance imaging in determining the size and shape of localized prostate cancer. Materials and Methods The subjects were 114 men who underwent multi-parametric magnetic resonance imaging before radical prostatectomy with patient specific mold processing of the specimen from 2013 to 2015. T2-weighted images were used to contour the prostate capsule and cancer suspicious regions of interest. The contours were used to design and 3-dimentional print custom molds, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
184
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(202 citation statements)
references
References 29 publications
14
184
0
4
Order By: Relevance
“…However, MRI is known to significantly underestimate lesion size compared to whole mount prostatectomy analysis, particularly so for ADC [28,29]. It is therefore possible that volumetric contouring of tumor volume based upon ADC underestimates the actual number of tumors that would be considered csPC if it was based on pathological tumor volume definition.…”
Section: Discussionmentioning
confidence: 99%
“…However, MRI is known to significantly underestimate lesion size compared to whole mount prostatectomy analysis, particularly so for ADC [28,29]. It is therefore possible that volumetric contouring of tumor volume based upon ADC underestimates the actual number of tumors that would be considered csPC if it was based on pathological tumor volume definition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent radiologic-pathologic correlation study of over 100 men using modern mpMRI demonstrated that pathologic prostate cancer foci had an average diameter 11 mm longer and a volume three times greater than based on mpMRI prediction (18). This may account for the reason that in our study, pre-treatment mpMRI MTD in the MSKCC model was not significantly different between the sub-groups.…”
Section: Resultsmentioning
confidence: 56%
“…In the report by Priester et al , tumors missed by MRI were significantly lower grade, smaller volume, and shorter in diameter than MRI-visible lesions (40). Thus, while these authors consider MRI to be insensitive for prostate cancer, they have in fact shown that MRI may reduce the issue of over diagnosis of clinically insignificant disease without meaningfully compromising the diagnosis of clinically significant cancer (40).…”
Section: Magnetic Resonance Imaging (Mri) Of the Prostatementioning
confidence: 98%